Dynamic Time Analysis of the Composite Shear Wall on the Grid-tube-type Double Steel Plate Wall with Infilled Concrete. Issue 1 (April 2021) - Li, Biqing; Li, Jinbao; Xu, Wenping
Abstract: In this paper, based on a 30-story building with frame-core tube structure system, three comparative schemes are established of reinforced concrete core tube construction, steel-reinforced concrete core tube construction and the combined shear wall core tube structure with the grid-tube-type double steel plate wall with infilled concrete are established, and the dynamic elastoplastic time history is analyzed. Research shows that under the influence of a severe earthquake, the lateral strength degradation and stiffness degradation are slow on the Joint structural system of concrete filled steel tubular frame and composite shear wall core tube structure with the grid-tube-type double steel plate wall with infilled concrete, so interlayer shear force and bottom shear force increase, structural lateral stiffness increased significantly, interlayer displacement angle reduces significantly, and it improves the seismic performance of tall building.